THE USE OF WORDWALL AS A MEDIUM FOR EVALUATING ARABIC LANGUAGE LEARNING FOR CLASS VII MTS NAHDHATUL WATHAN DINIYYAH ISLAMIYYAH TEBABAN: استخدام وسيلة “Wordwall” لتقييم تعليم اللغة العربية للصف السابع بمدرسة نحضة وطن الدينية الإسلامية المتوسطة الإسلامية في تبابان - Nadhifa, Shofiatin; Suparmanto, Suparmanto; Norratimah, Allya; Meliani, Meliani; Saputra, Hari (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
As times change, technological development is also accelerating, requiring the learning process to stay updated in line with technological advancements, especially in Arabic language learning. Arabic language learning is known to be difficult and tedious. Therefore, innovative and engaging methods and media are needed to enhance learning enthusiasm and minimize boredom among students during the learning process, leading to enjoyable and effective learning. In response to this, researchers used the Wordwall website as a learning medium for evaluating Arabic language learning. The purpose of this research is to introduce the Wordwall website, which can be used as an evaluation medium. The Wordwall media has many interesting features suitable for creating questions, making it effective for evaluating Arabic language learning and preventing students from getting bored with passive learning media. The method used in this research is descriptive qualitative with field research, employing data reduction techniques. The results show that the Wordwall media is very effective as an evaluation medium for Arabic language learning, as seen from the enthusiasm of students in responding to learning, creating a fun classroom environment and active students during the learning process. This media is very effective when applied at various school levels because it is rich in features that can be adjusted according to the level of the students. The use of Wordwall media as an evaluation medium has a positive impact on better learning outcomes because students are more active in the learning process.